It is better to light a candle than curse the darkness: the theme of spirituality/ religiosity in psychology congress - Michel, Renate Brigitte (2019)
The theme of spirituality/religiosity (S/R) is part of the everyday life of psychology professionals as well as discussions about the regulation of the ethical limits of professional practice. Through documentary research, the present study sought to investigate the contributions, modalities, and frequency with which this subject has been present in the titles of scientific productions of the most representative Psychology congresses in Brazil between the years of 2010 and 2016. In all, 25,768 scientific papers presented in the scientific programming of the 64 events available on online platforms were analyzed. The results show that only 0.59% (n = 154) of the Works found were related to the S/R theme. The subjects related to Social Psychology (n = 32) and Critical Reviews (n = 28) were the most frequent, followed by Developmental Psychology (n = 16), Theory/Theoretical Lines (n=16) and Health/Hospital Psychology (n = 15). The contributions of the Working Group on Psychology and Religion were also presented. It was therefore identified that, even for psychologists who are not specialists in Psychology of Religion, there is much to investigate regarding the interface between Psychology and Religion.